2001
DOI: 10.2176/nmc.41.399
|View full text |Cite
|
Sign up to set email alerts
|

Transient Ischemic Attack Due to Dissection of the Middle Cerebral Artery. Case Report.

Abstract: A 57-year-old man presented with a transient ischemic attack due to dissection of the middle cerebral artery. He suffered total aphasia and clouding of consciousness for several minutes. On admission, he was alert without neurological deficit. Magnetic resonance (MR) angiography and conventional angiography depicted irregularity and double lumen of the left middle cerebral artery. The diagnosis was dissection of the middle cerebral artery. After 1 month, he left our institute with no neurological deficit. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…MCA dissection with a patent pseudolumen should not be confused with fenestration. 9 On a selective cerebral angiogram, early branching MCA should not be misinterpreted as a fenestration because the branches may be superimposed in the anteroposterior projection. 8 In contrast, MR angiographic images are made from three-dimensional data.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…MCA dissection with a patent pseudolumen should not be confused with fenestration. 9 On a selective cerebral angiogram, early branching MCA should not be misinterpreted as a fenestration because the branches may be superimposed in the anteroposterior projection. 8 In contrast, MR angiographic images are made from three-dimensional data.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…Fusiform aneurysms in this study were found in the anterior circulation in 17 (77%) of the patients and in the posterior circulation in 23%. Dissection has been proposed as the main underlying cause of fusiform aneurysms and most commonly involves the posterior circulation, especially vertebral and basilar arteries 1,3,[5][6][7][8][9][10]15,16,19,20,[24][25][26]32,35) However, typical cases of dissecting aneurysm in the posterior circulation were excluded in this study. Dissecting aneurysms can originate in any regions of the anterior circulation, such as the ICA 1,29) , MCA 2,4,6,10,[13][14][15][16]22,26,30) , the ACA 3,10,[16][17][18]24,27,30,32,35) and rarely in the anterior choroidal artery 21) .…”
mentioning
confidence: 99%
“…Among the cases of infarction/TIA, six (19.4%) had images showing infarction in the cortical region, 12 (38.7%) had infarctions in the basal ganglia region, and 13 (41.9%) had infarctions in both regions [2, 10, 12, 15, 19-21, 24, 26, 28-30, 33-36,44, 51, 52,61-72]. Twentythree non-hemorrhagic cases were treated conservatively, including antiplatelet therapy (nine [39.1%]), anticoagulants (three [13.0%]), both antiplatelet and anticoagulant therapy (six [26.1%]), and no antithrombotic therapy (five [21.7%]) [10,12,15,19,24,26,30,33,34,36,44,52,60,61,63,66,68,69,71,72]. Tissue plasminogen activator (tPA) was administered in three non-hemorrhagic cases.…”
Section: Resultsmentioning
confidence: 99%